2014
DOI: 10.1016/j.ydbio.2014.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Migratory neural crest cell αN-catenin impacts chick trigeminal ganglia formation

Abstract: Neural crest cells are an embryonic cell population that is crucial for proper vertebrate development. Initially localized to the dorsal neural folds, premigratory neural crest cells undergo an epithelial-to-mesenchymal transition (EMT) and migrate to their final destinations in the developing embryo. Together with epidermally-derived placode cells, neural crest cells then form the cranial sensory ganglia of the peripheral nervous system. Our prior work has shown that αN-catenin, the neural subtype of the adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 32 publications
3
19
2
1
Order By: Relevance
“…Using the above Annexin A6 MO knockdown approach, we electroporated placodal ectoderm at HH9-10 and collected embryos at HH16-17 when trigeminal and epibranchial (here the geniculate) bipolar neurons are forming nerves within the ganglia. To evaluate neuronal and overall ganglion morphology, we performed immunohistochemistry for Tubb3 (Moody et al, 1989; Shiau et al, 2008; Wu et al, 2014), the class III β-tubulin in neurons either in their last stage of, or upon their exit, from the cell cycle (Moody et al, 1989), and examined tissue sections of forming trigeminal and geniculate ganglia (Figs. 3 and 4), and the trigeminal ganglion in lateral, whole-mount views (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using the above Annexin A6 MO knockdown approach, we electroporated placodal ectoderm at HH9-10 and collected embryos at HH16-17 when trigeminal and epibranchial (here the geniculate) bipolar neurons are forming nerves within the ganglia. To evaluate neuronal and overall ganglion morphology, we performed immunohistochemistry for Tubb3 (Moody et al, 1989; Shiau et al, 2008; Wu et al, 2014), the class III β-tubulin in neurons either in their last stage of, or upon their exit, from the cell cycle (Moody et al, 1989), and examined tissue sections of forming trigeminal and geniculate ganglia (Figs. 3 and 4), and the trigeminal ganglion in lateral, whole-mount views (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As such, we performed cell proliferation (phospho-histone H3 immunohistochemistry) and cell death (TUNEL) assays (Wu et al, 2014) (Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, any loss of migratory neural crest populations can impact cranial nerve formation by severing the cellular conduit for nascent axons growing out of the placodal cores of the cranial ganglia. In terms of molecular signals that can orchestrate cranial neural crest cell and placodal interactions, several studies have shown that cell adhesion molecules such as N-cadherin ( Cdh2 ) or αN-catenin ( Ctnna2 ) are important for cranial nerve integration [ 6 , 41 ]. Excessive N-cadherin ( Cdh2 ) expression in Xenopus results in abnormal aggregation and migration of neural crest cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%